230 Tracking late outgrowth endothelial cells in an acute arterial injury model. (5th June 2017) - Fujisawa, Takeshi; Mitchell, Andrew; Medine, Claire; Corral, Carlos Alcaide; Tavares, Adriana; Mills, Nicholas L; Hadoke, Patrick WF
Abstract : Aim: Late outgrowth endothelial cells (EOC) are strong contenders to be the true circulating endothelial progenitor cells since they are capable of clonogenic expansion, exhibit a mature endothelial phenotype, and contribute to angiogenesis in vivo . These cells may play a crucial role in the process of vascular repair, but whether they are able to accumulate at sites of vascular damage in vivo is not clear. We hypothesise that EOC, delivered locally or systemically, accumulate at, and incorporate into, a site of arterial injury. Methods: Experimental groups comprised systemic administration of the glucose analogue radiotracer 18 F-Flurodeoxyglucose (FDG) (Sys-Free) or FDG-labelled EOC (Sys-EOC), or local administration of free FDG (Local-Free) or FDG-labelled EOC (Local-EOC). EOC were isolated from peripheral blood from patients with coronary heart disease (n=3). Left femoral artery injury was achieved in male Sprague Dawley rats (300–350g) under general anaesthesia by inserting micro-renathane tubing via the popliteal artery. EOC were labelled with FDG (25 MBq/ml, 30 min, 37°C) and 1 million cells were administered either locally into the femoral artery or systemically via the tail vein (0.3–1.3 MBq, n=3 per group). Following injection of radiolabelled cells or free FDG, rats underwent dynamic PET scanning over 4 hours (Mediso nanoPET/CT scanner, Hungary). AuroVist and Fenestra (MediLumine Inc, Canada) were used as computed tomography vascular contrast agents. Images were analysed with PMOD software (PMOD, Switzerland) and standardised uptake values were calculated. Results: FDG radioactivity was successfully visualised by micro-PET/CT. The activity was distributed in the bladder, kidneys, heart, brain, lungs, spleen and liver (descending order). Radioactivity in the lungs was significantly higher (80 and 120 min) following systemic EOC administration compared with the other three groups (two-way ANOVA with Bonferroni post-test, p<0.001), and peak activity in the injured artery (55 min after administration) was significantly higher than in the non-injured right artery (two-way ANOVA with Bonferroni post-test, p<0.001). Following local EOC administration, radioactivity in the injured artery was significantly higher than in the non-injured right artery, or in the injured artery following local free FDG administration (two-way ANOVA with Bonferroni post-test, p<0.001). Radioactivity in the injured artery following local administration was considerably higher (~10 fold) than following systemic administration of either free FDG or labelled EOC. Conclusion: Preliminary analysis shows that EOC are able to target sites of vascular injury following systemic and local administration. These observations suggest that late outgrowth endothelial cells have the potential to contribute to vascular repair and regeneration.